2017
DOI: 10.18632/oncotarget.14716
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid inhibits glioblastoma multiforme cell growth via paraoxonase 2 expression

Abstract: We studied the potential mechanisms of valproic acid (VPA) in the treatment of glioblastoma multiforme (GBM). Using the human U87, GBM8401, and DBTRG-05MG GBM-derived cell lines, VPA at concentrations of 5 to 20 mM induced G2/M cell cycle arrest and increased the production of reactive oxygen species (ROS). Stress-related molecules such as paraoxonase 2 (PON2), cyclin B1, cdc2, and Bcl-xL were downregulated, but p27, p21 and Bim were upregulated by VPA treatment. VPA response element on the PON2 promoter was l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 60 publications
4
31
0
Order By: Relevance
“…In particular, the role played by PON2 as a metabolic regulator has been confirmed in a study carried out by Nagarajan et al In pancreatic ductal adenocarcinoma (PDAC) cell lines, the authors demonstrated that PON2 transcriptional repression is responsible for affecting the transport activity of glucose transporter 1 and subsequently, for an inhibition of PDAC tumor growth and metastasis [25]. Similarly, Tseng et al demonstrated that valproic acid, decreasing the PON2 expression, made glioblastoma multiforme-derived cell lines more sensitive to oxidative damage and cell death [27].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In particular, the role played by PON2 as a metabolic regulator has been confirmed in a study carried out by Nagarajan et al In pancreatic ductal adenocarcinoma (PDAC) cell lines, the authors demonstrated that PON2 transcriptional repression is responsible for affecting the transport activity of glucose transporter 1 and subsequently, for an inhibition of PDAC tumor growth and metastasis [25]. Similarly, Tseng et al demonstrated that valproic acid, decreasing the PON2 expression, made glioblastoma multiforme-derived cell lines more sensitive to oxidative damage and cell death [27].…”
Section: Discussionmentioning
confidence: 87%
“…Over the past years, many studies have described the involvement of PON2 in cancer. In particular, PON2 expression was shown to be increased in some solid tumors, including pancreatic cancer [26], glioblastoma multiforme [27], and recently BC [28]. Concerning bladder cancer, in our previous study, we demonstrated that the enzyme levels were significantly higher in tumors compared with adjacent normal looking tissue samples from BC patients.…”
Section: Introductionmentioning
confidence: 78%
“…Therefore, a higher effective concentration of VPA may be needed to exhibit cytotoxic effects in vivo . A higher concentration of VPA for in vitro and in vivo studies has been reported . Nevertheless, humans cannot handle such high concentrations of VPA.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the functional or molecular targeting effects of VPA in acute myeloid leukaemia (AML) cells as well as the relevant clinical trials suggested that clinical studies should investigate whether VPA, or any other drug, should be the preferred HDAC inhibitor in AML . More recent evidence indicating that VPA has anticancer activity has come from studies in cell lines from various cancers such as prostate, cervical, glioblastoma, pancreas, thyroid, breast and bladder . This distinct anticancer property of VPA is also believed to explain, at least partially, the mechanisms underpinning its teratogenic effects …”
Section: Resultsmentioning
confidence: 99%